2020
DOI: 10.3390/app10134546
|View full text |Cite
|
Sign up to set email alerts
|

A Novel High Gain Monopole Antenna Array for 60 GHz Millimeter-Wave Communications

Abstract: This paper presented the design and implementation of a 60 GHz single element monopole antenna as well as a two-element array made of two 60 GHz monopole antennas. The proposed antenna array was used for 5G applications with radiation characteristics that conformed to the requirements of wireless communication systems. The proposed single element was designed and optimized to work at 60 GHz with a bandwidth of 6.6 GHz (57.2–63.8 GHz) and a maximum gain of 11.6 dB. The design was optimized by double T-shaped st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The beamforming antennas help to improve the coverage, SNR, and effective beam steering [ 80 ]. We broadly categorize the 60 GHz smart beamforming antennas into three types: printed circuit board (PCB)-based antennas [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ], on-chip antennas [ 59 , 98 , 99 , 100 , 101 , 102 , 103 ], and low temperature co-fired ceramic (LTCC)-based antennas [ 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. We discuss these antennas here in detail.…”
Section: Antennas For Mmwave Industry 40 and Beyond Communicationmentioning
confidence: 99%
“…The beamforming antennas help to improve the coverage, SNR, and effective beam steering [ 80 ]. We broadly categorize the 60 GHz smart beamforming antennas into three types: printed circuit board (PCB)-based antennas [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ], on-chip antennas [ 59 , 98 , 99 , 100 , 101 , 102 , 103 ], and low temperature co-fired ceramic (LTCC)-based antennas [ 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. We discuss these antennas here in detail.…”
Section: Antennas For Mmwave Industry 40 and Beyond Communicationmentioning
confidence: 99%
“…Mneesy et al [2] presented the design and implementation of a 60 GHz single element monopole antenna as well as a two-element array made of two 60 GHz monopole antennas. The proposed antenna array was used for 5G applications with radiation characteristics that conformed to the requirements of wireless communication systems.…”
Section: A Novel High Gain Monopole Antenna Array For 60 Ghz Millimet...mentioning
confidence: 99%
“…Recently, various studies have been reported in literature to develop an effective antenna for the V-band communication spectrum [15][16][17][18][19][20][21][22][23][24][25][26]. In [15], a compact size button antenna for wearable applications is proposed; however, the antenna performance parameters, including bandwidth and gain, are compromised to achieve an electrically small antenna.…”
Section: Introductionmentioning
confidence: 99%
“…The antenna offers a high gain of 12 dB, having a wide operational bandwidth of 8 GHz at the cost of bigger dimensions. In [25] a conventional slotted patch antenna is designed, where DGS technique is used to attain high gain. However, use of multiple defects in patch and ground significantly increased the complexity.…”
Section: Introductionmentioning
confidence: 99%